Kawasaki disease: insights into the roles of T cells - Wang, Shuhui; Qian, Guanghui; Liu, Ying; Li, Xuan; Huang, Hongbiao; Sun, Ling; Lv, Haitao (Frontiers in Immunology, 2025)
Kawasaki disease (KD) is a systemic immune vasculitis characterized by fever and is a common cause of acquired heart disease in children. The etiology of KD remains unclear, but it is generally believed to be an amplified inflammatory cascade caused by the combined action of infection and genetic susceptibility factors. Changes in T lymphocyte subsets and their abnormal activation play an important role in the immune response to KD. This review delves into the critical role of T cells in the pathogenesis of KD, with a particular focus on how the expansion of CD8+ T cells and the imbalance between Th17 and Tregs contribute to IVIG resistance and persistent inflammation. Our analysis suggests that interventions targeting T cell function could potentially improve the clinical prognosis for KD patients. This provides specific directions for future therapeutic strategies, including the use of novel immunomodulatory approaches such as cyclosporine and IL-17/IL-23 inhibitors, aimed at providing new insights into the pathogenesis and treatment of KD.